(untitled) (Al-Farooq Journal of Sciences, 2026)
This research aims to shed light on the significant contributions of Libyan women in the fields of logistical support, nursing, and intelligence work, as well as their strategic mobilization, educational roles, and legendary resilience within fascist concentration camps. The study employs both the historical-analytical and descriptive methodologies to monitor events and analyze their national implications, utilizing diverse research tools including historical documents, memoirs, and the analysis of folk literature as a vital social record. The research concludes that Libyan women functioned as a sovereign institution that managed the war economy within the Adwar (military camps) and Nuju’ (rural settlements), ensuring the sustainability of the resistance for over two decades despite the rigorous blockade. Furthermore, the findings demonstrate the effectiveness of women in psychological warfare through the weapon of the word and the boosting of morale. Their steadfastness inside concentration camps (such as El Agheila, Al-Maqrun, and Brega) successfully thwarted the scorched earth strategy designed to break the collective will of society. The research recommends the integration of the Social History of Resistance into academic curricula and emphasizes the urgency of documenting oral histories to do justice to the Libyan female national memory.